Hemocompatible albumin-heparin coatings prepared by the layer-by-layer technique. The effect of layer ordering on thrombin inhibition and platelet adhesion - Houska, Milan; Brynda, Eduard; Solovyev, Andrey; Broucková, Adéla; Krízová, Petra; Vanícková, Martina; Dyr, Jan E (Journal of biomedical materials research. Part A, 2008)
Using the layer-by-layer technique, ELISA polystyrene plates were coated with multilayer assemblies of albumin with various heparins or with multilayer assemblies of albumin. The coatings containing heparin were tested for their ability to potentiate thrombin inhibition by antithrombin and its dependence on the layer arrangement. The order of activities of surface bound heparins matched their order in solution; however their activity was reduced to less than 10% due to binding. The increasing number of layers increased the activity of the coatings suggesting that heparin inside the assemblies is available for the interaction. The albumin-heparin assemblies overcoated with albumin layers preserved about half of heparin activity. Platelets adhered in similar amounts to albumin-heparin and albumin coatings; however, in both cases platelets adhered more to single layer than to multilayer coatings. The adhesion of platelets to single layer coatings was also affected by the crosslinking of the coatings; more platelets adhered to less crosslinked single layer coatings while multilayer coatings remained essentially unaffected by crosslinking. If the coatings were dried and reswollen, a substantial number of platelets adhered to the reconditioned single layer coatings but the two layer coatings were affected much less and the adhesion of platelets to the coatings with three layers was close to normal. A minimum of three albumin-heparin or albumin layers is apparently required to shield the underlying surface and to achieve proper functioning of the coatings.
Keywords: prasata; Cattle; Heparin; Swine; Spectroscopy, Fourier Transform Infrared; testování materiálů; Materials Testing; skot; adhezivita trombocytů; počet trombocytů; reagencia zkříženě vázaná; Platelet Adhesiveness; trombin; biokompatibilní potahované materiály; Coated Materials, Biocompatible; Animals; lidé; Thrombin; Platelet Count; Humans; zvířata; Cross-Linking Reagents; Serum Albumin, Bovine; sérový albumin hovězí; heparin; spektroskopie infračervená s Fourierovou transformací